Peran Self Efficacy Dan Perceived Organizational Support Terhadap Kinerja Pegawai Dinas Kesehatan Kabupaten Sanggau - Windi Pratiwi; ANGGA Hendharsa; Aisyah Aisyah (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2022)
The purpose of this study is to examine and analyze the effect of Self Efficacy and Perceived Organizational Support on the Performance of Employees of the Sanggau District Health Office. This type of research is included in quantitative research. The population in this study was 58 people, while the sample taken was 58 respondents determined based on the sensu technique. The variables in this study consisted of independent variables, namely self-efficacy and perceived organizational support, while the dependent variable was employee performance. Data collection techniques using questionnaires (questionnaires), literature studies and documentation studies. As for the data analysis technique using multiple regression analysis. This research has two output targets to be achieved, namely publishing scientific articles in accredited national or international journals as well as being a reference and evaluation medium for the Sanggau district health office in an effort to improve the performance of its employees. The results showed that Self Efficacy had a positive effect on employee performance (significance value 0.003 < 0.05) with a t value of (3.144) > t table (2.004) while Perceived Organizational Support had no effect on employee performance (significance value 0.221 > 0.05). ) with a value of t arithmetic (1.239) < t table (2.004), it can be concluded that the Perceived Organizational Support (X2) variable has no effect on the Performance of the Sanggau District Health Service Employees.